KERAGAMAN PEMAKNAAN MURABAHAH - Lies Ernawati; Unti Ludigdo; Ari Kamayanti (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2012)
The aims of this study is understand the meaning of murabahah financing by the BMT practitioners and scholars through intensionalisme hermeneutics. Intensionalisme hermeneutics used by practitioners and scholars to analyse how cultural and historical aspect of practitioners and scholars will murabaha interpretation. There were two informants from BMT Managemen, three informants from BMT customers, and four informants from scholars. The result shows, that scholars perceive murabahah as sale of mutual trust. The managements BMT perceive murabahah as a fair sale credit, mutually beneficial and have social aims. The BMT customers perceive murabahah as sale with recurring payments, easy and also has social objectives.